God in Nederland 1996-2006 - Dick Houtman (Religie & Samenleving)
A reading of God in Nederland 1996-2006 informs a critique of some intellectual routines in sociology of religion. On the positive side, the book goes beyond a simplistic onedimensional conception of “secularization” as declining Christian affiliations. It does so by adding analyses of post-Christian spirituality and Christian religion’s social and public significance. The latter is however reduced to the mere study of attitudes, thus neglecting real-life practices that may change in different directions. (Longitudinal) survey data moreover have inherent shortcomings that seem insufficiently acknowledged. Rather than addressing theoretically vital social and public significance of post-Christian spirituality, the authors stick to reproducing conventional (yet flawed and sociologically naive) claims about contemporary spirituality as privatized, fragmented, and individualized. It is finally pointed out that with the steady decline of Christian religiosity it becomes increasingly important to study worldviews of non-Christians and perhaps even wrap up sociology of religion in less narrowly defined sociology of culture.